Sexual Deviance in the View of the Qur'an: Analysis of Hamka's Interpretation in Tafsir al-Azhar - Javis Mi Dinata; Mohd Arifullah; Adi Iqbal (JIA (Jurnal Ilmu Agama), 2025)
This article aims to discuss the Qur'an's view on sexual deviance with reference to Hamka's Tafsir al-Azhar. One of the controversial issues in Indonesia is the emergence of the lesbian, gay, bisexual, and transgender (LGBT) community. They not only demand that their rights be respected but also fight for same-sex marriage to be legalized under marriage law. In the Qur'an, homosexuality is considered an abominable act that crosses boundaries. However, this issue seems to never cease being discussed, and it is becoming increasingly prevalent across all social strata. In fact, such behavior is strictly prohibited in the Qur'an and is clearly evident in the story of Prophet Lot. This study employs a qualitative method with a literature review (library research) approach. Through descriptive analysis using thematic interpretation, the research findings indicate that several verses of the Qur’an address homosexuality in connection with the story of the people of Prophet Lot. The Qur’an uses the term al-fāḥisyah to refer to same-sex sexual relations—whether between men or between women—which also signifies an act of extreme depravity. In Hamka's interpretation, this act is categorized as a despicable act that cannot be justified under any circumstances. This study contributes to the clear moral and ethical dimensions of al-Qur'an regarding al-fāḥisyah, while strengthening the classical and contemporary perspectives on the prohibition of deviant sexual behavior. This research also provides a foundation for strengthening the discourse on Islamic ethics in issues of sexuality, especially in the context of thematic (maudhu’i) readings of verses that are relevant to moral challenges in the modern era.